A New Annual 14C Dataset for Calibrating the Thera Eruption. Issue 4 (22nd August 2020) - Friedrich, Ronny; Kromer, Bernd; Wacker, Lukas; Olsen, Jesper; Remmele, Sabine; Lindauer, Susanne; Land, Alexander; Pearson, Charlotte
ABSTRACT: Annually resolved tree-ring samples of the time period 1625–1510 BCE were analyzed from the German oak tree-ring chronology. Blocks of the same tree rings were previously used to generate IntCal calibration data. The new dataset shows an offset to the calibration data IntCal13 of 24 years and resembles annual data for the same time period derived from tree-ring records in other growth locations. A subset of samples of the period 1625–1585 BCE was additionally measured in three other laboratories (ETH, AAR, AA) for quality control.